Paying the Price of War: United States Soldiers, Veterans, and Health Policy, 1917-1924 - Adler, Jessica L. (2013)
During eight turbulent years in the World War I era, policy makers, soldiers, and veterans laid the groundwork for the extension of government sponsored medical care to millions of former service members. In the process, they built a pillar of the American welfare state. Legislation and rehabilitation plans formulated shortly after the U.S. entered the Great War aimed to minimize the government's long-term obligations to veterans, but within less than a decade, those who had served gained conditional access to their own direct assistance agency and a national system of hospitals. This dissertation explains why that drastic transition occurred, and how one group of citizens won the right to obtain publicly funded health services. The story of wartime health policies has a variety of larger implications. It shows how veterans' welfare shifted from centering on pension and domicile care programs rooted in the nineteenth century to the provision of access to direct medical services; how rehabilitation and citizenship rights were conceived of and perceived at the dusk of the Progressive Era; how race, class, and gender shaped the health-related experiences of soldiers, veterans, and caregivers; how shifting ideals about hospitals and medical care influenced policy; and how interest groups capitalized on the tense political and social climate to bring about change. On a general level, an examination of the roots of a nationwide veterans' hospital system demonstrates how privileges were won in the twentieth century United States. It reveals a moment of state expansion, but it also illustrates the wider tendency of the U.S. government to award entitlements selectively. Given those factors, the policies that paved the way for the advent of a veterans' medical system deserve to be considered - alongside later federal assistance programs such as Social Security, Medicare, and Medicaid - as foundational in the development and shape of the American welfare state.